2017
DOI: 10.1094/phyto-02-17-0042-r
|View full text |Cite
|
Sign up to set email alerts
|

Citrus leprosis virus N: A New Dichorhavirus Causing Citrus Leprosis Disease

Abstract: Citrus leprosis (CL) is a viral disease endemic to the Western Hemisphere that produces local necrotic and chlorotic lesions on leaves, branches, and fruit and causes serious yield reduction in citrus orchards. Samples of sweet orange (Citrus × sinensis) trees showing CL symptoms were collected during a survey in noncommercial citrus areas in the southeast region of Brazil in 2013 to 2016. Transmission electron microscopy analyses of foliar lesions confirmed the presence of rod-like viral particles commonly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 56 publications
1
48
0
12
Order By: Relevance
“…Sabe-se atualmente que algumas linhagens de B. yothersi (tanto de citros quanto de cafeeiro) mantidas em laboratório no Instituto Biológico e no Centro de Citricultura do IAC, apresentam a capacidade de aquisição e transmissão de vírus, tanto da leprose dos citros quanto da mancha anular do cafeeiro (Ramos- González et al, 2016González et al, , 2017Nunes et al, 2017).…”
Section: Novas Abordagens Sobre O Complexo B Phoenicisunclassified
See 1 more Smart Citation
“…Sabe-se atualmente que algumas linhagens de B. yothersi (tanto de citros quanto de cafeeiro) mantidas em laboratório no Instituto Biológico e no Centro de Citricultura do IAC, apresentam a capacidade de aquisição e transmissão de vírus, tanto da leprose dos citros quanto da mancha anular do cafeeiro (Ramos- González et al, 2016González et al, , 2017Nunes et al, 2017).…”
Section: Novas Abordagens Sobre O Complexo B Phoenicisunclassified
“…A maioria das espécies que causam danos econômicos a plantas cultivadas, incluindo ornamentais, pertence ao gênero Brevipalpus (Jeppson et al, 1975;Childers & Rodrigues, 2011 (Chagas, 1973;Ochoa et al, 1994;Chagas et al, 2001Chagas et al, , 2003Childers et al, 2001;Rodrigues et al, 2008;Kitajima et al, 2010;Rodrigues & Childers, 2013;Alberti & Kitajima, 2014;Ramos-González et al, 2017;Nunes et al, 2017).…”
Section: Introductionunclassified
“…Lemon and sour orange have also been found naturally infected (Cruz‐Jaramillo et al., ; Roy et al., ,b) and Dieffenbachia and Swinglea are also alternative natural hosts. Sampling in non‐commercial C. sinensis orchards in Brazil identified that a further distinct rhabdovirus species with the proposed name CiLV‐N is causing there a nuclear‐type leprosis disease (Ramos‐Gonzalez et al., ). While not identified anywhere else, this finding confirms that further and diverse rhabdoviruses cause the leprosis disease.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…CiLV-N sensu novo is also known to have significant intraspecific diversity at the genome level, with divergence values of between 2% and 8% reported between four Brazilian isolates (Ramos-Gonzalez et al, 2017).…”
Section: Intraspecific Diversitymentioning
confidence: 99%
See 1 more Smart Citation